A Review on Development of Porous Aluminosilicate-Based Zeolite Adsorbent for Heavy Metal Pollution Treatment - Hakim, Muh. Supwatul; Iqbal, Rendy Muhamad; 'Adany, Fildzah; Putra, Riandy; Nitriany, Ici; Telaumbanua, Idam Sulastri; Sitorus, Raya Uli; Dewi, Rey Kamala (BRIN Publishing (Penerbit BRIN), 2024)
Heavy metal contamination endangers human health and has been identified as a global issue. The rising concentration of heavy metals in industrial and domestic wastewater has prompted the quest for effective technologies and treatments to remove them. Zeolite is a promising material for eliminating heavy metals from diverse sources that pollute wastewater. Zeolite is a crystal comprised of hydrated aluminosilicates of alkali and alkaline earth metals in a threedimensional crystal network composed of easily controllable SiO4 4− and AlO4 5− . This review focuses on the critical analysis of the application of several zeolites for the adsorption of heavy metals from wastewater, namely Cd(II), As(III and V), Cr(III and VI), Cu(II), Pb(II), Ni(II), Mn(II), and Hg(II). The results of heavy metal removal reported by zeolites are summarized, and the chemical modification of zeolites with acid/base/salt reagents, surfactants, and metal reagents has been investigated, compared, and discussed. The adsorption/desorption capabilities, systems, operational parameters, isotherms, and kinetics of zeolites are then explained and compared.